Meningkatkan Hasil Belajar PAK dengan Model Pembelajaran Problem Based Learning Fase B Tema "Aku Pribadi yang Unik" Kelas IV SDS Eka Tjipta Kenanga - Ardianus Anwarto (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve the learning outcomes of Catholic Religious Education (PAK) for fourth-grade students at SDS Eka Tjipta Kenanga on the theme "I Am a Unique Individual" by implementing the Problem Based Learning (PBL) model. PBL allows students to actively participate in learning, solve real-world problems, and develop critical thinking and creativity skills. The research method uses a quantitative approach with a classroom action research design conducted in two cycles. Each cycle includes planning, implementation, observation, and reflection. The results show a significant increase in student learning outcomes after the implementation of the PBL model, with average scores rising from the first to the second cycle. This study concludes that PBL is effective in enhancing students' understanding of concepts and active engagement in PAK learning.